An extendable and foldable staircase climbing trolley / Luqman Faris Mustafa Kamal - Mustafa Kamal, Luqman Faris (2023)
A fabrication of an extendable and foldable staircase climbing trolley will be proposed to this project. The objective and the main purpose of this project is to reduce the burden of people who live in high rise building such as an apartment. The extendable function enables users to carry more stuff at one time while the foldable function enables users to keep it in a compact space so that it doesn’t use up so much space. Some fabrication process of this product includes cutting, joining and welding. To conclude, people who live in a high rise building can carry stuff up the stairs easily